METODE COACHING GROW TERHADAP PELAKSANAAN PEMASANGAN INFUS: COACHING GROW METHOD AT INFUSION PRACTICE - Khotimah, Husnul; Nurjanah, Suci (LPPM STIKes Bahrul Ulum Jombang, 2023)
The Use of Coaching GROW Method on Infusion. Implementation of infusion that is not in accordance with standard procedures will be at risk of phlebitis. GROW Coaching is a strategy to increase awareness in changing behavior of nurses during infusion according to standard procedures. The purpose of this study is to attempt to change nurses' behavior in infusion so as to minimize the incidence of phlebitis in patients. This study uses a quasi-experimental method (Pre-Post test with Group Design) with 34 samples of nurse implementers, namely 17 treatment groups and 17 control groups. 170 patient samples, 85 treatment groups and 85 control group patients. The results of the Wilcoxon sighed rank test-test and post-test analysis in the treatment group showed p value= 0.05, in the control group with p value= 0.3 and mann-whitney test p value= 0.01 means there is significant differences in nurses implementing between grow coaching methods and without GROW coaching. This means that the implementation of SPO based on GROW coaching has an opportunity value of fewer plebitis. The results of this study suggest that nursing managers use the GROW coaching method so that they can improve skills in changing nurses' behavior in infusion and preventing phlebitis.